Specification for installation of gas fires, convector heaters, fire/back boilers and decorative fuel effect gas appliances. Decorative fuel effect gas appliances of heat input not exceeding 20 kW (2nd and 3rd family gases) Part 3, (15th April 2001) - British Standards Institution,
No abstract available